Web-системи для управління електронним документообігом - Топчій, А. Ю. (ХНУРЕ, 2019)
This paper is devoted to the study and solution of problems of document management systems and the creation of a web-based electronic document management system for further use in various fields. Here will be considered the application of the workflow system in practice, its relevance and need. This paper will describe the basic idea of workflow systems and the implementation of a web system. There will also be a comparative analysis of cloud services and the selection of the most suitable for implementation. As a conclusion, all desired parts of the web system and possible ways of improvement will be described here